Brominated flame-retardant polyamide composition for improving air trapping
By using zinc aromatic carboxylate and aromatic dicarboxylic acid units in the bromine flame retardant polyamide composition, the problem of "gas trapped" caused by the production of hydrogen bromide during processing of the bromine flame retardant is solved, and stable flame retardant performance and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411819186.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, bromine flame retardant is prone to decomposition during processing to produce hydrogen bromide, resulting in a "gas trap" phenomenon, affecting the quality of plastic products and equipment life, and may damage the flame retardant performance.
The aromatic zinc carboxylic acid is used as a synergistic agent to bind to the active center of the hydroperoxide to resist oxidation and prevent the production of hydrogen bromide. At the same time, the aromatic dicarboxylic acid unit is used to assist the flame retardant to play a synergistic flame retardant effect, reducing the addition ratio of bromine flame retardant.
It significantly improves the phenomenon of "gas trapping", maintains the stability of flame retardant properties, and improves the mechanical properties of thermoplastic materials, avoiding the disadvantages of high abrasiveness of zinc oxide.
Smart Images

Figure CN119613952A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, and specifically relates to a brominated flame-retardant polyamide composition for improving trapped gas. Background Art
[0002] As one of the most ideal materials for lightweight and efficient structural design, polyamide composites offer advantages such as high specific strength, corrosion resistance, fatigue resistance, excellent dimensional stability, and strong design capabilities. They have long been widely used in automotive applications (such as charging stations, signal connectors, high-voltage connectors, and BMS power battery management system peripherals) and electrical / electronic components (such as connectors, plugs, switches, and circuit breakers). In recent years, the increasing flame retardancy requirements for these products have necessitated the use of materials that meet UL94V-0 or even 5VA ratings.
[0003] Adding brominated flame retardants to thermoplastic compositions to achieve the desired flame retardancy is a proven technology. Brominated flame-retardant polyamide compositions are widely used in the automotive, industrial, and electronics / electrical sectors due to their excellent mechanical and flame retardant properties. Most brominated flame retardants are organic, including aliphatic and aromatic bromine-containing compounds. These flame retardants have good compatibility with polyamides and have minimal impact on the mechanical properties of the polymer itself.
[0004] Brominated flame retardants release bromine radicals during combustion, capturing free active radicals generated by thermal degradation of polymer materials. The resulting hydrogen bromide acts as a barrier to oxygen, thus suppressing combustion. At specific stages of the thermoplastic composition combustion process, such as during ignition or flame spread, the carbon-bromine bonds in the flame retardant break at high temperatures, releasing bromine radicals that effectively capture free active radicals generated by thermal degradation of the polymer material. This effectively reduces the concentration of free radicals, thereby mitigating or terminating the free radical chain reaction. Furthermore, the hydrogen bromide released by the decomposition of brominated flame retardants is non-flammable, effectively blocking oxygen and inhibiting the combustion reaction. However, polyamide has a high melting point and typically requires higher molding temperatures. Due to the low bond energy of the carbon-bromine bond, brominated flame retardants easily decompose during processing to produce hydrogen bromide, causing "gas entrapment." This can manifest as discoloration, scorching, and gas marks at the injection nozzle of injection molded products. This phenomenon is particularly severe when molding large parts or performing high-speed injection molding, where the material stagnates in the barrel for extended periods, shear rates are too high, and particularly when gate speeds are too fast, leading to intense frictional heating. This "gas entrapment" not only affects the quality of plastic products but also corrodes molds and melt processing equipment such as extruders and injection molding machines, and has environmental impacts. Therefore, halogen-based flame-retardant polyamide materials that improve gas entrapment are under extensive research.
[0005] The processing stability of thermoplastic compositions can be improved by adding processing antioxidants (such as phosphites, organic phosphinates, and sodium phenylphosphinate). These antioxidants can convert hydroperoxides (ROOH) into free radical-free, non-reactive, and thermally stable products, thereby inhibiting the chain branching reaction of the polymer to generate alkoxy and hydroxyl radicals during the autooxidation cycle. However, these processing antioxidants with strong reducing properties will react with antimony trioxide, which is an essential flame retardant synergist.
[0006] In addition, a common technical route is to add an acid scavenger to the thermoplastic composition to neutralize hydrogen bromide, such as patent document CN201880067367.1 provides a halogen-containing flame-retardant polyamide composition, adding zeolite or hydrotalcite as an acid scavenger; patent document CN200880016409.5 provides a flame-retardant polyamide resin composition resistant to metal corrosion, adding hydrotalcite and alkaline earth metal hydroxides. Adding acid scavengers (such as zeolite, hydrotalcite and alkaline earth metal hydroxides) can neutralize hydrogen bromide during processing and melt, improving the trapped gas problem, but this method will affect the flame retardant stability, because hydrogen bromide plays an important role in the flame suppression process of the polymer. If hydrogen bromide is excessively neutralized by the acid scavenger during combustion, the flame retardant performance of the composition will be unstable, and most acid scavengers (such as zeolite, hydrotalcite and alkaline earth metal hydroxides) have a negative impact on the mechanical strength of the thermoplastic composition.
[0007] Zinc ions have antioxidant properties and can bind to the active centers of hydroperoxides. Therefore, zinc compounds are often used to combat free radicals and slow polymer degradation during melt processing. For example, patent document CN201280044583.7 discloses a silver / zinc oxide mixture as a stabilizer for flame-retardant polyamides containing red phosphorus, demonstrating that zinc oxide as a stabilizer can significantly reduce phosphine evolution. Patent document CN201280051042.7 provides an improved polyamide composition for LED applications, using metal oxides such as zinc oxide to significantly improve the optical properties of LED products after high-temperature exposure. Although zinc compounds are not commonly used as the preferred antioxidant, zinc compounds, especially zinc oxide, are frequently used to stabilize high-temperature polymers and phosphorus-based flame retardants. However, zinc oxide's reactivity with hydrogen halides can also affect the flame retardant properties of the composition.
[0008] In summary, there is no brominated flame retardant composition in the prior art that can protect the carbon-bromine bond of the flame retardant during melt processing to prevent the generation of corrosive hydrogen bromide gas at this stage and without deteriorating the flame retardant stability and mechanical properties of thermoplastic materials. Summary of the Invention
[0009] The object of the present invention is to provide a brominated flame-retardant polyamide composition with improved gas entrapment, which can significantly improve gas entrapment and has stable flame retardant properties and excellent mechanical properties.
[0010] To achieve the above object, the present invention adopts the following technical solutions:
[0011] The present invention provides a brominated flame-retardant polyamide composition for improving gas entrapment, which comprises the following components in terms of mass percentage:
[0012]
[0013]
[0014] Or it may also include the following two components:
[0015] (E) Enhancer 5.0~50.0wt% (F) Other adjuvants 0.1~5.0wt%
[0016] The sum of components (A) to (F) is 100 wt%, and the components are prepared by melt blending through a single-screw or twin-screw extruder.
[0017] Component (A) is an aliphatic polyamide, which is a semi-crystalline polymer with a melting temperature of 150° C. to 300° C. The melting temperature is characterized by differential scanning calorimetry (DSC) with a heating and cooling rate of 10° C. / min.
[0018] The repeating units of the aliphatic polyamide are selected from one or more monomers of aliphatic dicarboxylic acid, aliphatic diamine having not less than four carbon atoms, and lactam.
[0019] The aliphatic dicarboxylic acid is selected from the group consisting of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanedioic acid, hexadecanedioic acid, octadecanedioic acid, and eicosanedioic acid.
[0020] The aliphatic diamine having not less than four carbon atoms is selected from the group consisting of butanediamine, pentamethylenediamine, ethylenediamine, tetramethylenediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, undecamethylenediamine, dodecamethylenediamine, tridecanediamine, tetradecanediamine, pentadecanediamine, hexadecanediamine, heptadecanediamine, octadecanediamine, nonadecanediamine, eicosanediamine, 2-methyl-1,8-octanediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine.
[0021] The lactam is selected from the group consisting of: ε-caprolactam, heptanolactam, undecanolactam, dodecanolactam, and α-pyrrolidone (butyrolactam).
[0022] The aliphatic polyamide and the monomers used are selected from the table below:
[0023]
[0024]
[0025] Preferably, the aliphatic polyamide is PA66 and / or PA6.
[0026] Component (B) is a brominated flame retardant. When a brominated flame retardant is introduced into a thermoplastic material, key requirements include minimizing the production of corrosive hydrogen bromide gas during melt processing of the thermoplastic material, such as during extrusion and molding. Meeting these requirements requires selecting an aromatic bromine-containing compound selected from the group consisting of decabromodiphenylethane, brominated epoxy resin, and brominated polystyrene, preferably brominated polystyrene, whose structure is shown in Formula I:
[0027]
[0028] Before bromination, the raw polystyrene is divided into free radical polystyrene and anionic polystyrene. The weight-average molecular weight (Mw) of free radical polystyrene ranges from 250,000 to 450,000, while that of anionic polystyrene ranges from 2,000 to 20,000. The high weight-average molecular weight of free radical polystyrene results in poor flow properties of the flame retardant after bromination. Furthermore, styrene produced by free radical polymerization contains approximately 1% residual unsaturated double bonds at the ends of its molecular chains, which easily form aliphatic chain substituents with the brominating agent during the bromination process. The carbon-bromine bonds in the aliphatic chain have relatively low bond energies and break upon heating to approximately 200°C, releasing hydrogen bromide, resulting in poor heat resistance. Therefore, the brominated polystyrene used is preferably anionic brominated polystyrene.
[0029] The brominated polystyrene requires an appropriate bromine content. If the bromine content is too low, a higher proportion of flame retardant must be added to achieve flame retardancy, which can affect the mechanical properties of the thermoplastic composition. Excessive bromine content can impair the flowability of the flame retardant, increasing the melt shear viscosity during melt processing and leading to the release of hydrogen bromide. The brominated polystyrene should have a bromine content of 60-75% by weight, preferably 65-70% by weight, to achieve a more balanced compromise between flame retardancy stability, high mechanical strength, ease of processing, and low gas entrapment in the thermoplastic composition.
[0030] The brominated polystyrene is produced using methods known in the industry and is categorized into fully brominated polystyrene and chlorinated brominated polystyrene based on their synthesis process. Fully brominated polystyrene has zero chlorine content and exhibits improved temperature resistance. The brominated polystyrene used in the present invention is preferably produced using the fully brominated process.
[0031] Component (C) is a synergist selected from one or a mixture of antimony trioxide, sodium antimonate, zinc borate, zinc stannate, magnesium silicate and clay (which can be natural or synthetic clay, such as hydrotalcite and layered double hydroxide, boehmite, kaolin), preferably antimony trioxide.
[0032] Component (D) is an aromatic zinc carboxylate, which is a compound of an aromatic dicarboxylic acid and a zinc ion.
[0033] The aromatic dicarboxylic acid is selected from the group consisting of terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, isophthalic acid, and terephthalic acid, preferably terephthalic acid, isophthalic acid, and 2,6-naphthalene dicarboxylic acid, more preferably terephthalic acid, as follows:
[0034] Terephthalic acid, CAS number is 100-21-0, molecular weight is 166.131, structural formula is
[0035]
[0036] Isophthalic acid, CAS number is 121-91-5, molecular weight is 166.131, structural formula is
[0037]
[0038] 1,4-Naphthalene dicarboxylic acid, CAS number is 605-70-9, molecular weight is 216.19, structural formula is
[0039]
[0040] 1,5-Naphthalenedicarboxylic acid, CAS No. 7315-96-0, molecular weight 216.19, structural formula
[0041]
[0042] 2,6-Naphthalenedicarboxylic acid, CAS No. 1141-38-4, molecular weight 216.19, structural formula
[0043]
[0044] 2,7-Naphthalenedicarboxylic acid, CAS number is 2089-89-6, molecular weight is 216.19, structural formula is
[0045]
[0046] Isophthalic acid, CAS number 19806-17-8, molecular weight 194.18, structural formula is as follows:
[0047]
[0048] Terephthalic acid, CAS number is 7325-46-4, molecular weight is 194.18, structural formula is
[0049]
[0050] The zinc source of the aromatic zinc carboxylate is selected from zinc carbonate, basic zinc carbonate and zinc nitrate, preferably zinc nitrate.
[0051] The aromatic zinc carboxylate is synthesized by a hydrothermal method, which includes:
[0052] (1) Using distilled water as a medium, an aromatic dicarboxylic acid and a zinc source are mixed at concentrations of 0.17 mol / L and 0.3 mol / L, respectively, to obtain an initial suspension. Subsequently, a sodium hydroxide solution with a concentration of 0.5 mol / L is used as a precipitant to adjust the pH of the initial suspension to neutral (pH 7). The suspension is placed in a heat-collecting magnetic stirrer and stirred in a constant temperature water bath at 80°C for 2 hours by adjusting the stirrer. The pH of the suspension is then adjusted to 8-9 using a sodium hydroxide precipitant and stirred for 1 hour.
[0053] (2) Transfer the solution obtained in step (1) into a pressure-resistant reaction vessel. After nitrogen purging, heat the reaction vessel to 200°C at a rate of 2°C / min and maintain the temperature for 100 hours to carry out the reaction.
[0054] (3) The water vapor in the reaction tank is discharged, and then the reaction tank is cooled to room temperature to obtain colorless flaky crystals. The crystals are filtered, washed with distilled water and dried to obtain aromatic zinc carboxylate.
[0055] Component (E) is a reinforcing agent selected from one or more of glass fibers, glass microspheres, carbon fibers and mineral fillers (such as talc, mica, kaolin, calcium carbonate, calcium silicate, magnesium carbonate), preferably glass fibers.
[0056] Component (F) is other auxiliary agents, which are selected from one or a mixture of two or more of toughening agents, colorants, release agents, heat stabilizers, flow improvers and crystallization accelerators.
[0057] The brominated flame-retardant polyamide composition for improving trapped gas is a melt-prepared blend, which is blended using a single-screw or twin-screw extruder. The extruder has an aspect ratio (L / D) of 32 to 52, preferably an L / D of 40 to 44, a processing temperature of 150 to 300° C., and a screw speed of 200 to 500 rpm.
[0058] Feeding order: Set a side feeding port at the rear section of the extruder for heating and melting, add component (B) brominated flame retardant and component (E) reinforcing agent, and add other material components through the main feeding port of the extruder after premixing.
[0059] Exhaust: 1 to 2 barrel openings in front of the extruder side feed port are used for normal pressure exhaust, and the second to last barrel opening in the die head is used for pressurized exhaust, with a pressure of 30 to 70 cm-Hg.
[0060] The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and then cut into granules by a pelletizer. The collected granules are dried to a moisture content of less than 0.1% and packaged.
[0061] The present invention also provides a flame-retardant polyamide product, which comprises the aforementioned brominated flame-retardant polyamide composition with improved gas entrapment.
[0062] The brominated flame-retardant polyamide composition for improving gas entrapment of the present invention mainly addresses the following technical problems:
[0063] 1. Brominated flame retardants suppress flames by releasing bromine free radicals during combustion to capture free radicals generated by the thermal degradation of polymer materials and releasing hydrogen bromide to block oxygen. However, due to the low bond energy of the carbon-bromine bond, brominated flame retardants easily decompose during processing to produce hydrogen bromide, which not only affects the quality of plastic products but also corrodes molds, extruders, and injection molding equipment, and has an environmental impact.
[0064] 2. Adding acid scavengers (such as zeolite, hydrotalcite and alkaline earth metal hydroxides) can neutralize hydrogen bromide during processing and melting, improving the gas entrapment problem. However, hydrogen bromide plays an important role in the polymer flame retardancy process. If hydrogen bromide is excessively neutralized by the acid scavenger during combustion, the flame retardant properties of the composition will be unstable. In addition, most acid scavengers have a negative impact on the mechanical strength of the thermoplastic composition.
[0065] 3. Zinc compounds have good antioxidant properties. Although they are not the preferred antioxidants, zinc compounds, especially zinc oxide, are often used to stabilize high-temperature polymers and phosphorus-based flame retardants. However, zinc oxide is reactive with hydrogen halides, and zinc oxide affects the flame retardant properties of the composition.
[0066] Compared with the prior art, the brominated flame-retardant polyamide composition of the present invention utilizes aromatic zinc carboxylate (a compound of aromatic dicarboxylic acid and zinc ion) to avoid the disadvantages of acid scavengers and zinc oxide in affecting the fire retardancy of thermoplastic compositions, and has the following beneficial effects:
[0067] First, the zinc ions in the compound can bind to the active center of hydroperoxide to counteract free radicals, and will not undergo hydrogen halide reaction, thus not affecting the flame retardant properties of the thermoplastic composition.
[0068] 2. The aromatic dicarboxylic acid unit of the compound can promote the carbonization of aliphatic polyamide, and is a good carbon-forming agent. It can play a good synergistic flame retardant role with flame retardants, reduce the addition ratio of brominated flame retardants, and further reduce the probability of hydrogen bromide release.
[0069] Third, the aromatic carboxylic acid zinc compound has good compatibility with polyamide polymers and avoids the disadvantage of high abrasiveness of zinc oxide, and will not degrade the mechanical properties of thermoplastic composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The curves show the stability effect of zinc terephthalate (Example 1) on the brominated flame-retardant polyamide composition.
[0071] Figure 2 The effect of zinc oxide (Comparative Example 2) and zinc terephthalate (Example 1) on the combustion performance of the brominated flame-retardant polyamide composition. DETAILED DESCRIPTION
[0072] To more fully understand and demonstrate the technical solutions, objectives, and advantages of the present invention, the technical effects produced by the present invention will be described in further detail and completely below with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. It should be noted that other embodiments obtained by those skilled in the art without departing from the concept of the present invention are all within the protection scope of the present invention.
[0073] The following commercially available materials were used in the examples and comparative examples:
[0074] PA66: Purchased from Invista, a manufacturer of polyamide 66, trade name U3600.
[0075] PA6: Polyamide 6, trade name LX275, purchased from Luxi Chemical Company.
[0076] PA610: Purchased from Huafeng Company, polyamide 610, trade name LC1624.
[0077] PA612: Purchased from Huafeng Company as polyamide 612, trade name LC1825.
[0078] PA46: Polyamide 46 purchased from Enhuali Company, trade name.
[0079] PA56: polyamide 56 purchased from Cathay Corporation, trade name E-2260.
[0080] PA1010: polyamide 1010 purchased from Guangyin Company.
[0081] PA11: polyamide 11 purchased from Arkema, with the trade name RILSANBMNO.
[0082] PA12: polyamide 12 purchased from Wanhua Company, trade name Wanamid L2000.
[0083] MIX-PA: refers to a mixture of PA610: PA612: PA46: PA56: PA1010: PA11: PA12 in the ratio of 1:1:1:1:1:1:1, obtained by Jinlun Company.
[0084] DBDPE: Decabromodiphenyl ethane purchased from Baili Company.
[0085] BEO: brominated epoxy resin purchased from Xingsheng Company, trade name EP-25K.
[0086] BPS-1: anionic brominated polystyrene purchased from Albemarle Corporation, trade name HP-5010, prepared by a full bromination process, with a bromine content of about 68% and a molecular weight of about 10,000.
[0087] BPS-2: free radical brominated polystyrene purchased from Matt Corporation, trade name XZ-6700, prepared by bromine chloride process, with a bromine content of about 67% and a molecular weight of about 360,000.
[0088] MIX-FR1: refers to a mixture of DBDPE:BEO:BPS-1:BPS-2 in a ratio of 1:1:1:1, obtained by Jinlun Company. The bromine content of the mixture is about 67.5%.
[0089] Sb2O3: Antimony trioxide purchased from Shanxing Company.
[0090] ZB: zinc borate purchased from Rio Tinto under the trade name Firebrake ZB.
[0091] ZS: zinc stannate purchased from Wimbolat, trade name Flamtard S.
[0092] NaSbO3: Purchased from Anter Company, which manufactures sodium antimonate.
[0093] TD: Magnesium silicate HTPultra5L purchased from Imifabi.
[0094] Clay: Washed ultrafine kaolin purchased from Carmin Company.
[0095] MIX-FR2: refers to a mixture of Sb2O3: ZB: ZS: NaSbO3: TD: Clay in a ratio of 1:1:1:1:1:1, obtained by Jinlun Company.
[0096] GF: glass fiber purchased from Shandong Fiberglass Company, trade name 995-10P, monofilament diameter 10 μm.
[0097] GB: glass microspheres purchased from 3M Company, trade name IM16K.
[0098] CF: carbon fiber purchased from Mitsubishi Rayon Co., Ltd., trade name TR06NL.
[0099] MIX-FILLER: refers to the mixture of GF:GB:CF:TD:Clay in the ratio of 1:1:1:1:1, obtained by Jinlun Company.
[0100] EPDM: maleic anhydride grafted ethylene propylene diene monomer rubber purchased from Nengzhiguang Company, trade name N428.
[0101] 1098: An antioxidant purchased from BASF, with the chemical name N,N'-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine.
[0102] CaSt2: calcium stearate purchased from Singapore Samyak Company, trade name SAK-CS-P.
[0103] DHT: hydrotalcite purchased from Kyowa Co., Ltd. of Japan, trade name DHT-4A.
[0104] ZnO: zinc oxide purchased from Zochem, trade name ZOCO100.
[0105] Preparation of component (D) aromatic zinc carboxylate used in the examples and comparative examples:
[0106] Step 1: Using distilled water as a medium, terephthalic acid and zinc nitrate are mixed at concentrations of 0.17 mol / L and 0.3 mol / L, respectively, to obtain an initial suspension. Subsequently, a 0.5 mol / L sodium hydroxide solution is used as a precipitant, and the pH of the initial suspension is adjusted to neutral (pH 7). The suspension is placed in a heat-collecting magnetic stirrer, and the stirrer is adjusted to stir the suspension in a constant temperature water bath at 80° C. for 2 hours. The pH of the suspension is then adjusted to 8-9 with a sodium hydroxide precipitant, and stirring is continued for 1 hour.
[0107] Step 2: The solution obtained in step 1 was transferred into a pressure-resistant reaction vessel. After nitrogen replacement, the reaction vessel was heated to 200° C. at a rate of 2° C. / min and maintained for 100 hours for reaction.
[0108] Step 3: Expel the water vapor in the reaction tank, then cool the reaction tank to room temperature to obtain colorless flaky crystals. Filter the crystals, wash with distilled water and dry them to obtain zinc terephthalate Zn-PTA.
[0109] According to the method of step 1 to step 3, zinc isophthalate, zinc 1,4-naphthalene dicarboxylate, zinc 1,5-naphthalene dicarboxylate, zinc 2,6-naphthalene dicarboxylate, zinc 2,7-naphthalene dicarboxylate, zinc isophthalate and zinc terephthalate are prepared respectively.
[0110] MIX-Zn: refers to a mixture of zinc isophthalate: zinc 1,4-naphthalene dicarboxylate: zinc 1,5-naphthalene dicarboxylate: zinc 2,6-naphthalene dicarboxylate: zinc 2,7-naphthalene dicarboxylate: zinc isophthalate: zinc terephthalate in a ratio of 1:1:1:1:1:1:1, obtained by Jinlun Company. The zinc content of the mixture is approximately 29.0%.
[0111] Preparation method
[0112] The components were weighed according to the composition shown in Table 1 and added to a twin-screw extruder for melt processing.
[0113] Extruder screw nominal diameter: 35mm;
[0114] Extruder screw length-to-diameter ratio (L / D): 40;
[0115] Processing temperature range: 150~300℃;
[0116] Main engine speed range: 300rpm.
[0117] Feeding order: Set a side feeding port at the rear section of the extruder for heating and melting, add component (B) brominated flame retardant and component (E) reinforcing agent, and add other material components through the main feeding port of the extruder after premixing.
[0118] Exhaust: 1 to 2 barrel openings in front of the extruder side feed port are used for normal pressure exhaust, and the second to last barrel opening in the die head is used for pressurized exhaust. The pressure range is 30 to 70 cm-Hg.
[0119] The melt from the twin-screw extruder is extruded through a die, cooled in a water tank, and then cut into granules by a pelletizer. The collected granules are dried to a moisture content of less than 0.1% and then packaged.
[0120] Specimen molding and conditioning
[0121] Specimen molding and conditioning are carried out according to the methods specified in ISO16396-2, with a molding melt temperature of 250-300°C and a mold temperature of 80-100°C. Mechanical properties testing: The specimens are conditioned in a 23°C environment for at least 16 hours, ensuring that the moisture content is less than 0.2%. Flammability testing: The specimens are subjected to two pre-conditioning conditions: 23°C / 50% RH / 48 hours and 70°C / 168 hours.
[0122] Mechanical properties testing
[0123] The tensile properties were tested according to the method specified in ISO527-2, with the test piece Type I, the pulling speed being 5 mm / min, and the testing instrument being a ZWICK Z010 universal testing machine.
[0124] Flammability test
[0125] The V-level vertical combustion test was carried out according to the method specified in UL94. The test piece size was 125mm×13.0mm×1.5mm, the flame height of the methane blowtorch was 20mm, the inner flame height was 10mm, and the test instrument was the ATLASHVUL2 combustion box.
[0126] Apply a flame 10±1mm below the midpoint of the bottom surface of the sample and maintain it for 10±0.5s. Then remove the blowtorch and use a timer to start measuring the afterflame time t1 and record whether there are molten droplets or dripping of burning materials / whether the cotton pad is ignited. When the sample flame goes out, immediately put the test flame under the sample again, keep the central axis of the blowtorch tube in a vertical position, and make the top of the blowtorch 10±1mm below the bottom of the sample for 10±0.5s. Then, immediately extinguish the blowtorch or move it far enough away from the sample so that it no longer affects the sample. At the same time, use a timer to start measuring the sample's afterflame time t2 and afterglow time t3, accurate to seconds. At the same time, record whether there are particles or molten droplets dripping from the sample / whether the cotton pad is ignited, and whether the sample burns the clamping fixture. Evaluate the vertical burning level of the sample according to the following assessment requirements (Table 1):
[0127] Table 1
[0128]
[0129]
[0130] Thermal stability test
[0131] Thermogravimetric analysis was performed according to ISO 11358-1 using a TAQ50 thermogravimetric analyzer. To simulate the molding process, a combination of a rising temperature method and a constant temperature method was used.
[0132] Heating method: The laboratory background temperature is controlled at (30±1)°C, the heating rate is 20°C / min, the temperature is raised from 30°C to 290°C, and the test time is from 0 to 13 minutes.
[0133] Constant temperature method: Maintain a constant temperature of 290°C for 5 minutes, and the test time is from the 13th to the 18th minute.
[0134] Injection molding end real machine test
[0135] An ARBURG ALLROUNDER 630S injection molding machine (2500 kN clamping force) was used, with barrel temperatures set at 260-300°C, hot runner temperature at 290°C, and mold temperature at 120°C. The mold was degassing according to the same maintenance requirements before injection molding of the thermoplastic composition. When "trapped air" defects appeared on the surface of the part, the test was terminated and the mold was re-serviced. The number of days in production was recorded as one mold cleaning cycle.
[0136] Examples and Comparative Examples
[0137] Tables 2 and 3 list the performance of the compositions of various examples.
[0138] Comparative Examples 1 and 2 were used to verify the performance differences between free radical brominated polystyrene (BPS-2) prepared by the bromine chloride process and anionic brominated polystyrene (BPS-1) prepared by the full bromine process in thermoplastic compositions. It was found that BPS-1 exhibited better flame retardant, mechanical and thermal stability properties.
[0139] In Example 1 and Example 3, 0.5% zinc terephthalate was added to Comparative Example 1 and Comparative Example 2, respectively, and it was found that both the flame retardancy and the thermal stability were significantly improved.
[0140] Comparative Example 1, Comparative Example 3, Comparative Example 4 and Example 1 verify the performance difference shown by the zinc terephthalate prepared by adding zinc oxide, hydrotalcite and the present invention in the brominated flame retardant polyamide composition, and find that zinc oxide, hydrotalcite and zinc terephthalate all extend the mold cleaning cycle days. Under the same addition ratio, zinc oxide effect is optimal, zinc terephthalate effect is second, and hydrotalcite effect is the worst. Zinc oxide and hydrotalcite all have deterioration effect on the mechanical properties and flame retardant properties of thermoplastic composition, and zinc terephthalate does not deteriorate mechanical properties, and can significantly improve flame retardant properties. In addition, zinc oxide and zinc terephthalate all significantly improve the thermal stability of thermoplastic composition, and the thermal weight loss data of composition after adding the above substances significantly reduce, but hydrotalcite is not found to improve the thermal stability of composition, and analysis hydrotalcite can only provide acid scavenger effect, and cannot provide thermal stability effect for composition as zinc compound.
[0141] As a zinc compound, zinc oxide outperforms zinc terephthalate in thermal stability tests and mold clearing cycles at the same proportion. This is due to the difference in zinc ion content between the compounds; zinc oxide contains 80.3% zinc ions, while zinc terephthalate contains only 28.5%. This indicates that increasing the zinc ion content improves the thermal stability of thermoplastic compositions. However, not all zinc ions participate in the anti-free radical oxidation process. Comparative Example 2, with added zinc oxide, showed a significant increase in the burning time of the thermoplastic composition, indicating that some zinc oxide acts as an acid scavenger to neutralize hydrogen halides during combustion, leading to a deterioration in flame retardant performance. Zinc terephthalate exhibits better compatibility with polyamide polymers. Even with a lower zinc ion content compared to zinc oxide, it achieves thermal stability similar to zinc oxide at the same proportion without affecting flame retardant properties.
[0142] Comparative Examples 5 and 4 through 8 provided different zinc ion / bromine formulations, and the flame retardant and thermal stability properties of the thermoplastic compositions were observed. It was found that 0.3% zinc terephthalate (corresponding to a zinc ion / bromine content ratio of 61 ppm / %) significantly improved both flame retardant and thermal stability properties. Further improvement was observed as the zinc ion / bromine content ratio continued to increase. However, when the zinc terephthalate content was 2%–5% (corresponding to a zinc ion / bromine content ratio of 449–1178 ppm / %), the improvement in thermal stability became less significant. All examples with increased proportions of aromatic carboxylic acid zinc showed a sustained improvement in flame retardant properties.
[0143] Table 2: Comparison of performance of different stabilizers / acid scavengers / bromostyrenes
[0144]
[0145]
[0146] Table 3: Comparison of performance of different zinc ion / bromine content ratios in thermoplastic compositions
[0147]
[0148]
[0149] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A brominated flame-retardant polyamide composition for improving gas entrapment, characterized in that: According to the percentage by mass, it includes the following components: Or also include the following components: The sum of components (A) to (F) is 100 wt%, and the components are prepared by melt blending in a single-screw or twin-screw extruder.
2. The brominated flame-retardant polyamide composition for improving gas entrapment according to claim 1, characterized in that: The aliphatic polyamide is a semi-crystalline polymer with a melting temperature of 150 to 300° C. and is selected from one or a mixture of two or more of PA6, PA66, PA610, PA612, PA46, PA56, PA1010, PA11 and PA12.
3. The brominated flame-retardant polyamide composition for improving gas entrapment according to claim 1, characterized in that: The brominated flame retardant is selected from one of decabromodiphenylethane, brominated epoxy resin and brominated polystyrene.
4. The brominated flame-retardant polyamide composition for improving gas entrapment according to claim 3, characterized in that: The brominated flame retardant is brominated polystyrene, wherein the bromine content is 60wt% to 75wt%.
5. The brominated flame-retardant polyamide composition with improved gas entrapment according to claim 1, characterized in that: The flame retardant synergist is selected from antimony trioxide, sodium antimonate, zinc borate, zinc stannate, magnesium silicate, clay, or a mixture of two or more thereof; wherein the clay is natural clay or synthetic clay, and is selected from hydrotalcite, layered double hydroxide, boehmite, kaolin, or a mixture of two or more thereof.
6. The brominated flame-retardant polyamide composition with improved gas entrapment according to claim 1, characterized in that: The aromatic zinc carboxylate is a compound of an aromatic dicarboxylic acid and a zinc ion, wherein: The aromatic dicarboxylic acid is selected from the group consisting of terephthalic acid, isophthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, isophthalic acid, terephthalic acid; and / or the zinc source of the aromatic zinc carboxylate is selected from one of zinc carbonate, basic zinc carbonate and zinc nitrate.
7. The brominated flame-retardant polyamide composition with improved gas entrapment according to claim 6, characterized in that: The aromatic dicarboxylic acid is selected from one or a mixture of two or more of terephthalic acid, isophthalic acid and 2,6-naphthalene dicarboxylic acid; and / or the zinc source of the aromatic zinc carboxylate is zinc nitrate.
8. The brominated flame-retardant polyamide composition with improved gas entrapment according to claim 6, characterized in that: In the brominated flame-retardant polyamide composition, the content of zinc / bromine elements is 60 to 1200 ppm / %.
9. The brominated flame-retardant polyamide composition with improved gas entrapment according to claim 1, characterized in that: The reinforcing agent is selected from one or a mixture of two or more of glass fiber, glass microbeads, carbon fiber and mineral filler; and / or the auxiliary agent is selected from one or a mixture of two or more of toughening agent, colorant, release agent, heat stabilizer, flow improver and crystallization promoter.
10. The brominated flame-retardant polyamide composition with improved gas entrapment according to any one of claims 1 to 9, characterized in that: The aliphatic polyamide is PA6 and / or PA66; And / or the brominated flame retardant is anionic brominated polystyrene with a weight average molecular weight Mw of 2000 to 20000, prepared by a full bromine process; and / or the flame retardant synergist is antimony trioxide; and / or the aromatic zinc carboxylate is a compound synthesized from terephthalic acid and zinc nitrate by a hydrothermal method; and / or the reinforcing agent is glass fiber; And / or the single-screw or twin-screw extruder has an aspect ratio L / D of 32 to 52, a processing temperature of 150 to 300° C., and a screw speed of 200 to 500 rpm.
Citation Information
Patent Citations
Flame retardant polyamide resin composition
CN101802098B
Silver / zinc-oxide mixtures as stabilizers for flame-retardant polyamides containing red phosphorus
CN103797058A
Improved polyamide compositions for LED applications
CN103890040A
Halogen-containing flame-retardant polyamide compositions
CN111225947B
Cited By
PA66 composition as well as preparation method and application thereof
CN122445187A